Application of Public Domain Satellite-Based DEMs in Natural Hazard Modeling - Akbari, Abolghasem; Noram Irwan, Ramli; Ngien, S. K.; Reyhane, Azimi (IJESD, 2016)
This paper describe the specification and applications of public domain satellite-based DEMs including SRTM and ASTER-GDEM which, are globally available free. From the result, it was found that several advantages were recognized for public domain satellite–based DEMs including ease of accessibility, elimination of institutional bureaucracy, unlimited coverage and adequate spatial resolution.